PENGELOLAAN ALOKASI DANA DESA DITINJAU DARI KOMPETENSI APARATUR, KOMITMEN ORGANISASI, DAN PARTISIPASI MASYARAKAT - Firma Sulistiyowati; Yulita, Ima Kristina; Wardhani, Aurelia Melinda Nisita (Universitas Katolik Indonesia Atma Jaya, 2024)
Funds allocated to villages have the potential to be misused by village apparatus in terms of management so that the goal of alleviating poverty for marginalized communities cannot be achieved. This study aims to examine the influence of apparatus competence, organizational commitment, and community participation on the management of village fund allocations. The approach used in this study is a quantitative approach. Data collection was carried out using a questionnaire. The variables in this study include independent variables, namely Apparatus Competence, Organizational Commitment, and Community Participation. The dependent variable is Village Fund Allocation Management. The research was conducted on village apparatus and community representatives in the villages of Bantul Regency using multiple linear regression data analysis techniques. The results of this study indicate that apparatus competence and community participation affect the management of village fund allocations, while apparatus commitment does not affect the management of village fund allocations. The implication of this research is the achievement of village fund allocation management that is able to prevent misuse of the village apparatus and involves community participation because it takes into account the competence of the village apparatus.